Numerical and Experimental Study on Seakeeping Performance of a High-Speed Trimaran with T-foil in Head Waves - Li Ang; Li Yunbo (Polish Maritime Research, 2019)
The longitudinal motion characteristics of a slender trimaran equipped with and without a T-foil near the bow are investigated by experimental and numerical methods. Computational fluid dynamics ( CFD) method is used in this study. The seakeeping characteristics such as heave, pitch and vertical acceleration in head regular waves are analyzed in various wave conditions. Numerical simulations have been validated by comparisons with experimental tests. The influence of large wave amplitudes and size of T-foil on the longitudinal motion of trimaran are analyzed. The present systematic study demonstrates that the numerical results are in a reasonable agreement with the experimental data. The research implied that the longitudinal motion response values are greatly reduced with the use of T-foil.